Who is in charge when I have a headache? Brazilian version of the Headache-Specific Locus of Control Scale - VIEIRA, Rebeca Veras de Andrade; KOWACS, Fernando; LONDERO, Renata Gomes; BAREA, Liselotte Menke; GRASSI, Vanise; RODRIGUES, Luiz Eduardo Barcellos; SANTOS, Eduardo Pacheco; GOMES, William Barbosa; GAUER, Gustavo (Arquivos de Neuro-Psiquiatria, 2021)
Background: Headache-Specific Locus of Control (LOC) refers to individuals’ beliefs about their control over the onset, course and consequences of headaches. LOC beliefs have been associated with depression, coping strategies, headache-related disability and treatment outcomes. Objective: To test the cross-cultural adaptation and psychometric properties of a Brazilian version of the Headache-Specific Locus of Control Scale (HSLC). Methods: One hundred and thirty-four migraine outpatients completed the HSLC and provided measurements of psychopathological symptoms, pain catastrophizing, depression, anxiety, quality of life and headache-related disability. Results: The three-factor structure of the HSLC (LOC-P, LOC-C and LOC-I) was confirmed in the Brazilian sample. The instrument showed good internal consistency, with Cronbach's α of 0.77 for total HSLC and 0.70, 0.83 and 0.87, for LOC-P, LOC-C and LOC-I, respectively. LOC-C correlated with headache frequency and headache intensity. Along with headache intensity, depression and pain catastrophizing, LOC-I accounted for 45% of the variance (adjusted R2=0.45; F=12.97; p<0.01) in headache-related disability. Conclusions: The Brazilian version of the HSLC is a valid and reliable measure of headache-specific LOC beliefs. It is important to consider the balance between the three LOCs for each individual, instead of interpreting them separately.
Keywords: Migraine Disorders; Validation Study; Depression; Anxiety; Catastrophization